Sixteen year retrospective analysis of rheumatic and non-rheumatic heart disease patients undergoing valve procedures at Groote Schuur Hospital first incidence single aortic and mitral valve replacement - Ogunrombi, Akinwumi Babatunde (Division of Cardiology, 2015)
Includes abstract.